EFEK PILATES TERHADAP KESEIMBANGAN PADA ATLET OLAHRAGA PERMAINAN : Literature Review - Yulita Budi Hapsari (2020)
Balance is an important component of every movement in sports. An athlete must have a good balance to keep their body stable both when they moving or not. The purpose of this study is to determine the effect Pilates on balance in sport game athletes. The method of this study are collecting literature review data, the literature review use electronic databases such as Google Schoolar, Science Direct, PubMed and Research Gate by using certain keywords in 2015-2020 time span. From the literature search result, only 4 articles were found that fit the inclusion criteria. The article assessed the quality of the methodology using the PEDro. The research sample in general shows a significant value, p <0.05 Star Excursion Balance Test anterior CG 2.39±0.9 dan EG 4.76±0.9, medial CG 1.84±0.7 dan EG 3.69±0.13, posterior CG 1.94±0.6 dan EG 4.56±0.11, lateral CG 2.26±0.9 dan EG 4.40±0.9.After reviewing the literature, the result show that Pilates with right dose can improve the balance in sport game athletes as measured using the Star Excursion Balance Test.